On late style: poetry - Annunciação (UFBA), Viviane Carvalho da (ANTARES: Letras e Humanidades, 2013)
The present paper is concerned with how "late style" works in poetry written by the two acclaimed writers, Derek Walcott and Seamus Heaney. The term "late style" was firstly used by Theodor Adorno in order to characterize Ludwig van Beethoven's later work. According to him, late works "are [...] bitter and spiny, they do not surrender themselves to mere delectation. They lack all the harmony [...] and they show more traces of history than of growth" (ADORNO, 2002, p. 564). In order to understand how this process works in poetry, I am going to examine the volumes White Egrets (2010) by Walcott and Human Chain (2010), by Heaney. The conclusion that is reached is that the poetical subjectivity turns into a creative force, which unites irreconcilable realities in a discourse that questions clichés of identity, post-colonialism, multiculturalism, national belonging and ethical and historical responsibility.